DAMPAK KOMUNIKASI INTERPERSONAL PADA KEPUASAN PELANGGAN DI CV. TIRTA MAKMUR UNGARAN JAWA TENGAH - Erna Nur Wahidah; C. Susmono Widagdo; Enik Rahayu; Hendrajaya; Hendrajaya Hendrajaya (Journal of Innovation Research and Knowledge, 2025)
Investigating the connection between interpersonal communication and customer satisfaction at CV in Tirta Makmur Ungaran, Central Java, is the goal of this study. This study's research methodology is quantitative. The research's data source was primary survey data obtained through the distribution of questionnaires. Customers of CV. Tirta Makmur Ungaran, Central Java are the research subjects. Non-probability sampling was used to obtain data, and 100 respondents were given questionnaires. Validity and reliability tests are used in this study's testing, and the t-test is used for hypothesis testing and basic linear analysis tests in the analytic tools. The study's findings show that interpersonal communication significantly and favorably affects customer satisfaction at CV. Tirta Makmur Ungaran, Central Java.